Functional exploration of colorectal cancer genomes using Drosophila. - Bangi, E.; Murgia, C.; Teague, A.G.; Sansom, O.J.; Cagan, R.L. (Nature communications, 2016)
The multigenic nature of human tumours presents a fundamental challenge for cancer drug discovery. Here we use Drosophila to generate 32 multigenic models of colon cancer using patient data from The Cancer Genome Atlas. These models recapitulate key features of human cancer, often as emergent properties of multigenic combinations. Multigenic models such as ras p53 pten apc exhibit emergent resistance to a panel of cancer-relevant drugs. Exploring one drug in detail, we identify a mechanism of resistance for the PI3K pathway inhibitor BEZ235. We use this data to identify a combinatorial therapy that circumvents this resistance through a two-step process of emergent pathway dependence and sensitivity we term 'induced dependence'. This approach is effective in cultured human tumour cells, xenografts and mouse models of colorectal cancer. These data demonstrate how multigenic animal models that reference cancer genomes can provide an effective approach for developing novel targeted therapies.